SMART CITY TRAFFIC CONTROL SYSTEM - A, Satheeshkumar; M, Abirami; A, Hari Thirunavukkarsu; S, Sree Vignesh; Manavaalan, G. (Journal of Trends in Computer Science and Smart Technology, 2023)
Every city in the downtown areas around the world faces a major problem due to heavy traffic, especially during the peak hours. Traditional traffic signals used in manging the traffic allots a fixed time for managing the traffic in a junction of a four way or a two-way crossroads and cannot adjust to account for changes in traffic. The proposed system provides a scheduled crossing time that is automatically adjusted based on the traffic. A long green light is assigned using the proposed to the particular side of the crossroad that faces heavy traffic. For this the suggested model uses IR sensors installed in every 5 meters of the road to detect objects.
Keywords: JSFiddle; cellular Network; archetype; traditional industries